Predisposing Variables in Children with Risk of Disruptive Mood: A Clinical Case–Control Study - GÖKSU, MUHSİNE; YILDIRIM, ALPER (My University, 2023)
Disruptive mood dysregulation disorder (DMDD) is defined in the DSM-V as frequent, severe temper outbursts that significantly impair functioning in different environments. This was a second-stage of follow-up study, conducted to screen the frequency of DMDD in an elementary school. In the firststage of our study, 453 children between ages 7–11 were evaluated in terms of DMDD high-risk with Children Behavior Check List (CBCL). Of the children, 30 high-risk and 30 low-risk children for DMDD according to CBCL agreed to participate this clinical case–control study. Diagnoses of anxiety disorder, attention deficit and hyperactivity disorder (ADHD), and oppositional defiant disorder were more common among children in the high-risk group than the control group. Symptom Checklist-90-Revised (SCL-90-R) mothers’ interpersonal, anger, and paranoid subscale scores were higher in the DMDD highrisk group than the control group. Children in the DMDD high-risk group scored higher than the control group in all SRS subscales. In the Diagnostic Analysis of Nonverbal Accuracy (DANVA) test, the DMDD high-risk group had higher error rates for fearful and intense facial expressions. Multiple linear regression analysis showed that having a diagnosis of ADHD, high maternal SCL-90-R anger score, and presence of a paternal psychiatric diagnosis increased the high-risk of DMDD.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyal Psikoloji; Klinik Psikolojisi; Sosyoloji; Genel Sosyoloji ve Metedoloji; Hukuk; Social Sciences and Humanities; Psychology; Social Psychology; Clinical Psychology; Sociology; General Sociology and Methodology; Law; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, SOSYAL; PSİKOLOJİ, KLİNİK; SOSYOLOJİ; HUKUK; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, SOCIAL; PSYCHOLOGY, CLINICAL; SOCIOLOGY; LAW; Sosyal Bilimler ve Beşeri Bilimler; Klinik Psikoloji; Sosyoloji ve Siyaset Bilimi; Social Sciences & Humanities; Sociology and Political Science